ORAL AND CRANIOFACIAL CHARACTERISTICS OF UNTREATED ADULT UNILATERAL CLEFT LIP AND PALATE INDIVIDUALS - Ravi, M. S. (Journal of Health and Allied Sciences NU, 2012)
Introduction: Cleft lip and palate anomaly being the common congenital defect having significant effects on the facial morphology, function and growth and development of the individual, requires a detailed study of the Dental and craniofacial characteristics.Design and setting: The study is conducted in a hospital set up and the subjects were selected at random as per the inclusion criterion. Objectiveof study was to evaluate the craniofacial and Dental morphology in untreated unilateral cleft lip and palate (UCLP) individuals.Materials and Methods: A total of 64 individuals in the age group of 15-28 yrs were selected and grouped in to two groups; Cleft group consisting of 13 males and 19 females having untreated UCLP and another group of 16 male and 16female non cleft individuals. Study cast, lateral cephalogram and frontal cephalogram analysis were carried out .The obtained data were analyzed using ANOVA to compare the values between the groups.Result: Significant differences in cranio- facial characteristics were noted between the cleft and non cleft individuals. These differences were more pronounced in sagittal plane and less in transverse plane.Conclusion: Significant differences exist in the cranio- facial morphology between the untreated UCLP individuals and non cleft individuals.
Keywords: lateral Cephalogram; Frontal Cephalogram; Cleft; Cranio facial morphology